2012
DOI: 10.1371/journal.pone.0034467
|View full text |Cite
|
Sign up to set email alerts
|

Dual Anti-OX40/IL-2 Therapy Augments Tumor Immunotherapy via IL-2R-Mediated Regulation of OX40 Expression

Abstract: The provision of T cell co-stimulation via members of the TNFR super-family, including OX40 (CD134) and 4-1BB (CD137), provides critical signals that promote T cell survival and differentiation. Recent studies have demonstrated that ligation of OX40 can augment T cell-mediated anti-tumor immunity in pre-clinical models and more importantly, OX40 agonists are under clinical development for cancer immunotherapy. OX40 is of particular interest as a therapeutic target as it is not expressed on naïve T cells but ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
1
38
0
2
Order By: Relevance
“…Given these properties, IL-2/S4B6 complexes could be used therapeutically in metastatic malignancies and chronic viral infection. In support of this notion, several groups have reported favorable results using IL-2/S4B6 complexes either as a monotherapy or in combination with another agent (such as Toll-like receptor ligand, agonist anti-OX40 mAb, or peptide vaccine) in various cancer models, including B16 melanoma, Lewis lung carcinoma, MC38 colon carcinoma, MCA-205 sarcoma, and TRAMP-C1 prostate carcinoma [31,[48][49][50][51][52][53]. Moreover, IL-2/S4B6 complexes have shown efficacy in models of acute and chronic infection [54,55].…”
Section: Il-2/mab Complexesmentioning
confidence: 93%
“…Given these properties, IL-2/S4B6 complexes could be used therapeutically in metastatic malignancies and chronic viral infection. In support of this notion, several groups have reported favorable results using IL-2/S4B6 complexes either as a monotherapy or in combination with another agent (such as Toll-like receptor ligand, agonist anti-OX40 mAb, or peptide vaccine) in various cancer models, including B16 melanoma, Lewis lung carcinoma, MC38 colon carcinoma, MCA-205 sarcoma, and TRAMP-C1 prostate carcinoma [31,[48][49][50][51][52][53]. Moreover, IL-2/S4B6 complexes have shown efficacy in models of acute and chronic infection [54,55].…”
Section: Il-2/mab Complexesmentioning
confidence: 93%
“…OX40 (CD134 or TNFRSF4) is a costimulatory molecule expressed on the surface of activated T lymphocytes (84). Agonists of OX40 have been used successfully in a variety of preclinical tumor models with promising results (85)(86)(87)(88), and a variety of combinatorial strategies to increase anti-OX40 antibody therapy with vaccines, chemotherapy, radiotherapy, and immunotherapy have been explored (79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). A mouse anti-human OX40 mAb has shown activity in nonhuman primates and has been tested in phase I clinical trials in 30 patients at different dosages with minimal toxicity although patients showed elevated levels of neutralizing human anti-mouse antibodies (92).…”
Section: Agonist Antibodies To Tnfr Molecules That Costimulate T and mentioning
confidence: 99%
“…However, trials combining anti-PD-1 antibodies with ipilimumab and prostate cancer vaccines are planned for 2015. Most recently, research with OX40 ligation in combination with CTLA-4 blockade showed antitumor activity in a nonimmunogenic murine model of CRPCA, which has been predictive of ipilimumab clinical activity in mCRPCA (39). Anti-OX40 ligation in combination with ipilimumab for mCRPC is slated to enter the clinic soon.…”
Section: Dc-based Immunotherapymentioning
confidence: 99%